Perbandingan Pendidikan Islam Dengan Pendidikan Umum Di Indonesia - Priyono, Cipto Duwi; Hidayatullah, Rully; Hankam, Arief Arafat; Wandi, Joni Indra; Aisyah, Siti (Institut Agama Islam Sumatera Barat Pariaman, 2023)
Education is a key element in the social, economic and cultural development of a nation. In Indonesia, there are two main education systems, namely Islamic education and general education, which have significant differences in aspects of curriculum, teaching methods and social impact. This study aims to conduct an in-depth comparison between these two education systems to better understand the differences and their impact on Indonesian society. This research uses descriptive analysis methods and literature studies to collect data related to the curriculum, teaching methods, and social impacts of the two education systems. The results of the analysis show that significant differences exist in the Islamic education curriculum which focuses on religious and moral education, while general education has a broader curriculum and covers various subjects. Teaching methods in Islamic education place more emphasis on religious and cultural values, while general education tends to use conventional teaching methods. The social impact of these two education systems also has striking differences. Islamic education tends to promote religious values ??and religious identity, while general education is more oriented towards global and secular aspects. This can influence people's understanding and perception of their religion and culture, as well as influence social integration in a heterogeneous society. This research provides valuable insight into the differences and impacts of the two main education systems in Indonesia. The results can be a reference for making more holistic and inclusive education policies, which combine religious values ??and cultural diversity, while ensuring that education remains relevant to global demands and social developments in the future.